Hilangnya Minat Generasi Muda Untuk Bertani: Young Generation Losing Interest in Farming - Adilla , Zahrani Crisna; Rozaki, Zuhud; Wulandari, Retno; Nurlita, Mita (Universitas Muhammadiyah Yogyakarta, 2024)
Being blessed with fertile land and suitable for planting various crops is a gift from the creator. Indonesia is often dubbed as the world's granary because it is one of the largest rice-producing countries in the world. Indonesia is an agricultural country based on the statement of the Central Statistics Agency (BPS) which states that the number of Indonesian farmers reached 31.70 in 2013. The agricultural sector is one of the country's foreign exchange that helps the economy. Farming activities are one of the livelihoods of most Indonesian people. The productivity of Indonesian farmers who are still productive ranges from more than 40-54 years old with traditional methods. Meanwhile, the younger generation who are more aware of technology are now reluctant to become farmers simply because of the prestige factor that exists in each individual, the fear before trying and underestimating the farming profession. Not being able to utilize technology wisely is a negative impact of technological advances that cause users to become lazy, but there is a positive impact behind it, one of which is spreading agricultural information throughout the earth quickly.